Proposed Marketing Strategy to Increase Brand Awareness and Sales of Portable Smart Projector (A Case Study of Samsung the Freestyle) - Nabilla Rizky Ramadhani; Harimukti Wandebori (Jurnal Indonesia Sosial Teknologi, 2025)
Samsung The Freestyle, a portable smart projector launched by Samsung, has faced challenges in increasing brand awareness and sales in the Indonesian market. Initially introduced in January 2022, Samsung The Freestyle garnered significant interest during its pre-order phase. However, despite its innovative features, the product experienced a decline in sales performance over time. This research aims to identify the internal and external factors influencing the performance of Samsung The Freestyle, employing both quantitative and qualitative approaches. Primary data were gathered through interviews with Samsung Electronics Indonesia employees and surveys with questionnaires, while secondary data were collected from reports, articles, and social media. The study also utilizes comprehensive consumer analysis, including segmentation, targeting, and positioning (STP), level of awareness, perceptions and level of satisfaction. External analysis was conducted by analyzing the general environment, industrial environment, and competitor analysis. Resource analysis and value chain analysis were performed to obtain the internal factors. A SWOT analysis identified the strengths, weaknesses, opportunities, and threats, leading to the formulation of the TOWS matrix for strategic recommendations. Based on the analysis, the appropriate corporate strategy for Samsung Electronic Indonesia is growth, the proposed business strategy for The Freestyle is differentiation, and marketing strategies are proposed through the 4P marketing mix (Product, Price, Promotion, and Place). Strategies encompass product diversification with competitive pricing, market development to the mid to premium segment, branding on social media, conducting strategic partnerships, interesting promotions, and improving distribution networks and product availability